2015
DOI: 10.1002/adma.201504609
|View full text |Cite
|
Sign up to set email alerts
|

Spatioselective Electrochemical and Photoelectrochemical Functionalization of Silicon Microwires with Axial p/n Junctions

Abstract: The spatioselective functionalization of silicon microwires with axial p/n junctions is achieved using the electronic properties of the junction. (Photo)electrochemical deposition of metals is demonstrated at the bottom and top of the wires in the dark and light, respectively. The junction depletion layer remains unmodified, which allows its visualization and comparison with theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Figure A shows that the good photocurrent reproducibility can be observed in TiO 2 NBs and TiO 2 homojunction. And compared with that of TiO 2 NBs, TiO 2 homojunction exhibits a higher photocurrent intensity indicating that the TiO 2 homojunction catalyst possesses a superior charge separation property and transfer ability, which is consistent with the result of PL analysis. The weak PL intensity and enhanced photocurrent in TiO 2 homojunction further confirmed that the high efficiency of this dendritic homojunction structure on suspension of photo‐generated carrier recombination and promotion of carrier transportation with the simulated solar light irradiation.…”
Section: Resultssupporting
confidence: 82%
“…Figure A shows that the good photocurrent reproducibility can be observed in TiO 2 NBs and TiO 2 homojunction. And compared with that of TiO 2 NBs, TiO 2 homojunction exhibits a higher photocurrent intensity indicating that the TiO 2 homojunction catalyst possesses a superior charge separation property and transfer ability, which is consistent with the result of PL analysis. The weak PL intensity and enhanced photocurrent in TiO 2 homojunction further confirmed that the high efficiency of this dendritic homojunction structure on suspension of photo‐generated carrier recombination and promotion of carrier transportation with the simulated solar light irradiation.…”
Section: Resultssupporting
confidence: 82%
“…Other reported results strengthen this hypothesis. In earlier work, we have observed an inversed gradient of electrodeposited Pt particles from a solution containing H 2 PtCl 6 on an array of microwires (with 7 μm length, 4 μm diameter and 2 μm spacing). There, the deposited Pt particle density was also higher at the bottom than the top.…”
Section: Results and Discussionmentioning
confidence: 95%
“…For example, Milbrat et al . have developed a method for the spatioselective functionalization of silicon microwires with axial p‐n junctions . The charges directed by the junction, either in the dark or under illumination, were used to electrochemically deposit silver or platinum NPs in a spatially selective manner.…”
Section: Introductionmentioning
confidence: 99%